2021
DOI: 10.3390/molecules26020418
|View full text |Cite
|
Sign up to set email alerts
|

Four Novel Phenanthrene Derivatives with α-Glucosidase Inhibitory Activity from Gastrochilus bellinus

Abstract: Four new phenanthrene derivatives, gastrobellinols A-D (1–4), were isolated from the methanolic extract of Gastrochilus bellinus (Rchb.f.) Kuntze, along with eleven known phenolic compounds including agrostophyllin (5), agrostophyllidin (6), coniferyl aldehyde (7), 4-hydroxybenzaldehyde (8), agrostophyllone (9), gigantol (10), 4-(methoxylmethyl)phenol (11), syringaldehyde (12), 1-(4′-hydroxybenzyl)-imbricartin (13), 6-methoxycoelonin (14), and imbricatin (15). Their structures were determined by spectroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The roots of this plant have been used as traditional Thai medicine to alleviate liver dysfunction and nephropathy [ 2 , 8 ]. In our continuing studies on bioactive compounds from orchids [ 9 , 10 ], we have explored the chemical constituents from the aerial parts of C. ensifolium with no previous reports on the chemical investigation. In the present study, a methanolic extract prepared from the aerial parts of this plant exhibited a significant cytotoxic effect against various cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The roots of this plant have been used as traditional Thai medicine to alleviate liver dysfunction and nephropathy [ 2 , 8 ]. In our continuing studies on bioactive compounds from orchids [ 9 , 10 ], we have explored the chemical constituents from the aerial parts of C. ensifolium with no previous reports on the chemical investigation. In the present study, a methanolic extract prepared from the aerial parts of this plant exhibited a significant cytotoxic effect against various cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…30 Syringaldehyde is abundantly present in lignocellulosic (Mori Folium, Apricot pits, Gastrochilus bellinus, etc.) [31][32][33][34][35] and has wide applications in biomedicine (monitoring of disease-related markers, modification activity of antimicrobial agents, etc.). [36][37][38][39] In this study, syringaldehyde was chosen as the raw material for the design and synthesis of S1 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Syringaldehyde is abundantly present in lignocellulosic (Mori Folium, Apricot pits, Gastrochilus bellinus , etc. ) 31–35 and has wide applications in biomedicine (monitoring of disease‐related markers, modification activity of antimicrobial agents, etc.) 36–39 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that orchids produce various classes of secondary metabolites, such as stilbenoids, anthraquinones, flavonoids, terpenoids, steroids, and alkaloids (Nongdam, 2014). So far, the AGIs obtained from Orchidaceae can be chemically classified into 7 major groups: (i) bibenzyl derivatives, for example, 4,5-dihydroxy-3,4-dimethoxybibenzyl and dendrofalconerol A from Dendrobium tortile, gigantol from Dendrobium devonianum, batatasin III and dendrosinen B from Dendrobium infundibulum, and dendroscabrol B from Dendrobium scabrilingue (Limpanit et al, 2016a;Na Ranong et al, 2019;Sarakulwattana et al, 2020;Sun et al, 2014); (ii) phenanthrene-related compounds, for example, 4,5-dihydroxy-2-methoxy-9,10-dihydrophenanthrene from Dendrobium christyanum, lusianthridin, and coelonin from Dendrobium scabrilingue (San et al, 2020;Sarakulwattana et al, 2020), bobulretin A from Bulbophyllum retusiusculum (Sun et al, 2018), gastrobellinol C from Gastrochilus bellinus (San et al, 2021), and 5-methoxy-7-hydroxy-9,10-dihydro-1,4-phenanthrenequinone from Dendrobium formosum (Inthongkaew et al, 2017); (iii) flavonoids, for example, rutin from Pholida chinensis, naringenin from Dendrobium densiflorum, and 5-hydroxy-3-…”
Section: Chapter I Introductionmentioning
confidence: 99%
“…(v) lignans, for example, syringaresinol-4-O-D-glucopyranoside from Flickingeria fimbriata (Chen et al, 2018); (vi) phenylpropanoids, for example, coniferyl aldehyde from Gastrochilus bellinus (San et al, 2021); and (vii) benzylmalate glycosides, for example, arundinoside D from Arundina graminifolia (Auberon et al, 2019). These are illustrated in Table 1 and Figure 1.…”
Section: Chapter I Introductionmentioning
confidence: 99%